2022
DOI: 10.1002/adfm.202211269
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Memristor Constructed by 2D Cadmium Phosphorus Trichalcogenide for Artificial Synapse and Logic Operation

Abstract: The development of advanced microelectronics requires new device architecture and multi‐functionality. Low‐dimensional material is considered as a powerful candidate to construct new devices. In this work, a flexible memristor is fabricated utilizing 2D cadmium phosphorus trichalcogenide nanosheets as the functional layer. The memristor exhibits excellent resistive switching performance under different radius and over 103 bending times. The device mechanism is systematically investigated, and the synaptic plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…This characteristic was simulated by applying two successive pre-pulses with Δ t from 2 to 22 ms in the Pt/Ga 2 O 3 /n + Si memristor. The PPF index ([( A 2 – A 1 )/ A 1 ] × 100% = C 1 .25em exp ( t τ 1 ) + C 2 .25em exp ( t τ 2 ) , where A 1 and A 2 were the conductance readouts after the first and second pulses and C 1 and C 2 were the initial facilitation magnitudes) , as the function of Δ t is fitted in Figure d. The two fitting time constants, τ 1 (5.029 ms) and τ 2 (17.211 ms), corresponded to the fast and slow decaying terms, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic was simulated by applying two successive pre-pulses with Δ t from 2 to 22 ms in the Pt/Ga 2 O 3 /n + Si memristor. The PPF index ([( A 2 – A 1 )/ A 1 ] × 100% = C 1 .25em exp ( t τ 1 ) + C 2 .25em exp ( t τ 2 ) , where A 1 and A 2 were the conductance readouts after the first and second pulses and C 1 and C 2 were the initial facilitation magnitudes) , as the function of Δ t is fitted in Figure d. The two fitting time constants, τ 1 (5.029 ms) and τ 2 (17.211 ms), corresponded to the fast and slow decaying terms, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…, where A 1 and A 2 were the conductance readouts after the first and second pulses and C 1 and C 2 were the initial facilitation magnitudes) 45,46 as the function of Δt is fitted in Figure 4d. The two fitting time constants, τ 1 (5.029 ms) and τ 2 (17.211 ms), corresponded to the fast and slow decaying terms, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to substrates, 2D materials (e.g., graphene, 2D transition metal dichalcogenides, h-BN, 2D cadmium phosphorus trichalcogenide) with atomic layer thickness and ultrathin organic films with molecular-scale thickness has gradually become popular choices for flexible synaptic devices due to their intrinsic bendability. The 1D nanowire or network structure also are competitive candidates for strain-resistant synaptic devices, such as carbon nanotube networks , and conductive polymer nanofibers. , Yang et al showed a 1D organic charge-transfer complex well-aligned array on the polyimide (PI) substrate that could confine the conducting filaments to reliable performance .…”
Section: Realization Of Flexible/stretchable Synaptic Devicesmentioning
confidence: 99%
“…Recently, Chen and coauthors developed a fiber-based memristor network comprising fragile Ag/MoS 2 /HfAlO x /carbon nanotubes (CNTs), providing a novel pathway toward the development of flexible in-memory computing textile systems. 246 In addition to substrates, 2D materials (e.g., graphene, 247 2D transition metal dichalcogenides, 248 h-BN, 249 2D cadmium phosphorus trichalcogenide 250 ) with atomic layer thickness and ultrathin organic films with molecular-scale thickness has gradually become popular choices for flexible synaptic devices due to their intrinsic bendability. The 1D nanowire or network structure also are competitive candidates for strain-resistant synaptic devices, such as carbon nanotube networks 251,252 and conductive polymer nanofibers.…”
Section: Structural Engineering For Flexible Artificial Synaptic Devicesmentioning
confidence: 99%
“…6 In addition, 2D layered materials are flexible, which offers great possibilities for their applications in flexible electronics. 7,8 Moreover, the stacking order or twist angle between the layers provides a new degree of freedom, which may induce a new quantum effect. 9,10 Currently, 2D vdW heterostructures have become a focus of material science research.…”
Section: Introductionmentioning
confidence: 99%